134k views
2 votes
This is a linear equations question so pls help me I’m dying of stress thank you! ^^

This is a linear equations question so pls help me I’m dying of stress thank you! ^^-example-1
User SeanR
by
5.0k points

2 Answers

6 votes

Answer:

the answer to this problem is D:(-2,4)(1,1)

User Lazyhammer
by
5.1k points
1 vote

Answer:

B

Explanation:

y = x² → (1)

y = 3x - 2 → (2)

substitute y = x² into (2)

x² = 3x - 2 ← subtract 3x - 2 from both sides

x² - 3x + 2 = 0 ← in standard form

(x - 1)(x - 2) = 0 ← in factored form

equate each factor to zero and solve for x

x - 1 = 0 ⇒ x = 1

x - 2 = 0 ⇒ x = 2

substitute these values into (2) for corresponding values of y

x = 1 : y = 3(1) - 2 = 3 - 2 = 1 ⇒ (1, 1 )

x = 2 : y = 3(2) - 2 = 6 - 2 = 4 ⇒ (2, 4 )

User Csabinho
by
5.0k points